2022
DOI: 10.1007/s10461-022-03606-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding PrEP Acceptability Among Priority Populations: Results from a Qualitative Study of Potential Users in Central Uganda

Abstract: Daily oral pre-exposure prophylaxis (PrEP) can safely and effectively prevent HIV acquisition in HIV-negative individuals. However, uptake of PrEP has been suboptimal in sub-Saharan Africa. The goal of this qualitative study was to identify facilitators of and barriers to PrEP acceptability among target users not taking PrEP. Fifty-nine individuals belonging to Ugandan priority populations participated in a single in-depth interview. Participants perceived themselves as being at high risk for HIV acquisition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…The common reports of stigma hindering uptake of PrEP among our study participants were similar to the findings from other studies [11,31]. For example, research on uptake of PrEP has reported that stigma associated with being labelled as HIV-infected and being suspected of infidelity or promiscuity, was a barrier to uptake of PrEP [11,32,33].…”
Section: Plos Onesupporting
confidence: 86%
See 3 more Smart Citations
“…The common reports of stigma hindering uptake of PrEP among our study participants were similar to the findings from other studies [11,31]. For example, research on uptake of PrEP has reported that stigma associated with being labelled as HIV-infected and being suspected of infidelity or promiscuity, was a barrier to uptake of PrEP [11,32,33].…”
Section: Plos Onesupporting
confidence: 86%
“…Our study findings show that individuals at high risk of HIV infection who were enrolled in an HIV vaccine preparedness study in Uganda were interested in taking oral PrEP because they understood that it would protect them against acquisition of HIV, a finding corroborated by other recent work in Uganda [11,23,24]. However, among those who had chosen to start PrEP many did not initiate and/or persist with the drug.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Despite emerging qualitative literature around PrEP-related stigma and its impacts [14][15][16][17][18][19][20], quantitative assessment of PrEP-related stigma remains sparse. This is particularly true in SSA, where PrEP implementation continues to scale up among diverse populations.…”
Section: Introductionmentioning
confidence: 99%